2020
DOI: 10.1038/s41598-020-76119-w
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological effects of kratom (Mitragyna speciosa): In vitro studies with implications for efficacy and drug interactions

Abstract: The safety and efficacy of kratom (Mitragyna speciosa) for treatment of pain is highly controversial. Kratom produces more than 40 structurally related alkaloids, but most studies have focused on just two of these, mitragynine and 7-hydroxymitragynine. Here, we profiled 53 commercial kratom products using untargeted LC–MS metabolomics, revealing two distinct chemotypes that contain different levels of the alkaloid speciofoline. Both chemotypes were confirmed with DNA barcoding to be M. speciosa. To evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 52 publications
7
98
0
1
Order By: Relevance
“…It is obvious from the preceding section that mitragynine and other related alkaloids are substrates for multiple CYP isoforms and hence may interfere with metabolisms of clinical drugs. Preclinical research on mitragynine and related alkaloids on DDI is limited but has been gaining attention within the last 10 years ( Hanapi et al, 2013 ; Lim et al, 2013 ; Kamble et al, 2020 ; Todd et al, 2020 ; Tanna et al, 2021 ). Here, the focus is on the effect of mitragynine and related alkaloids on DMEs from in vitro preclinical research, and their utility to predict clinical DDI.…”
Section: Interactions With Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious from the preceding section that mitragynine and other related alkaloids are substrates for multiple CYP isoforms and hence may interfere with metabolisms of clinical drugs. Preclinical research on mitragynine and related alkaloids on DDI is limited but has been gaining attention within the last 10 years ( Hanapi et al, 2013 ; Lim et al, 2013 ; Kamble et al, 2020 ; Todd et al, 2020 ; Tanna et al, 2021 ). Here, the focus is on the effect of mitragynine and related alkaloids on DMEs from in vitro preclinical research, and their utility to predict clinical DDI.…”
Section: Interactions With Enzymesmentioning
confidence: 99%
“…Mitragynine has been repeatedly shown in different in vitro studies to potently inhibit CYP2D6 with K i values ranging from 1.1 to 13 µM ( Hanapi et al, 2013 ; Kamble et al, 2020 ; Todd et al, 2020 ; Tanna et al, 2021 ). Using the static mechanistic model, Tanna et al (2021) revealed that kratom preparation sold in the U.S. market could cause significant DDI with drugs primarily metabolized by CYP2D6 if more than 9 g kratom extract containing 83 mg mitragynine ( Todd et al, 2020 ) was taken with AUCR > 1.25.…”
Section: Interactions With Enzymesmentioning
confidence: 99%
“…All of these databases are in the public domain. The data that were extracted and used for these analyses are included as a supplemental table . neurotransmitter systems in the central nervous system (Kruegel et al, 2016;Varadi et al, 2016;Obeng et al, 2020;Todd et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The major active alkaloid found in kratom is mitragynine, along with more than 40 other minor alkaloids. [11][12][13][14][15][16] In recent years, we have become interested in the chemistry and pharmacology of kratom alkaloids as probes to understand opioid receptor function. 11,[17][18][19][20][21][22][23] Previous reports from our group reported that mitragynine (possessing an indole core), its oxidation product 7OH (possessing an indolenine core), and mitragynine pseudoindoxyl (MP, a skeletal rearrangement product of 7OH with a spiro-pseudoindoxyl core) (Figure 1A), are all opioid antinociceptive agents 18,19 and Gprotein biased MOR agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SC11, SC12 and SC13 (all C9 substituted 7OH analogs) were chosen as leads from the series of compounds synthesized. SC11-13 were evaluated in the PathHunter assay, 18,22 which we and others 12 have previously used to measure β-arrestin2 activity of the parent natural products. In this assay, like morphine (Emax=31%), SC11-13 were found to recruit β-arrestin2 with greatly reduced efficacy (Emax<20%) compared to DAMGO (Appendix 1-Figure 1C).…”
Section: Introductionmentioning
confidence: 99%